Factors Related to the First Antenatal Care Visit (KI MURNI) at the Akle Regional Community Health Center - Paulina Upa, Nekha Helsa; Andriyanti, Andriyanti; Djuari, Lilik (Rifa'Institute, 2026)
Introduction: The maternal mortality rate (MMR) in Indonesia declined to 189 per 100,000 live births in 2020. However, this figure remains significantly above the Sustainable Development Goals (SDG) target of 70 per 100,000 live births by 2030. One essential strategy to reduce MMR is to increase the coverage of antenatal care (ANC), particularly the initial visit (first ANC), which should occur before 12 weeks of gestation to facilitate early detection of pregnancy risks and prevent complications. Objective: This study aimed to analyze the factors associated with first ANC visits at Puskesmas Akle. Methods: This was an observational analytic study employing a cross-sectional design. The population included 138 pregnant women, with a sample of 50 participants selected through simple random sampling. Data were collected from medical records and analyzed using the chi-square test. Results and Discussion: The findings revealed that only 42% of respondents attended first ANC visits before 12 weeks of gestation. Significant associations were found between maternal age (p = 0.041) and parity (p = 0.014) and compliance with first ANC visits. However, no significant association was identified between maternal employment status (p = 0.976) and early ANC attendance. Conclusion: Compliance with early ANC visits remains low and is influenced by maternal age, parity, and accessibility to health facilities. Targeted health education and strengthened ANC services are essential to improving access for pregnant women, particularly those in underserved or hard-to-reach areas